Akibat Hukum Perjanjian Kawin terhadap Pihak Ketiga dalam Perspektif Putusan Mahkamah Konstitusi No. 69/PUU-XIII/2015 - Putu Trisna Witariyani; I Nyoman Sujana; Ni Made Puspasutari Ujianti (Fakultas Hukum, Universitas Warmadewa, 2021)
Property problems in marriage often occur. With this, the couple can make a marriage agreement for those who want to separate their marital assets. One of the marriage agreement arrangements, which is mentioned in paragraph (1), namely in Article 29 of Law Number 1 of 1974 concerning marriage states that a marriage agreement can be made before the marriage takes place and binds a third party as long as the third party is involved. However, after the issuance of the Constitutional Court Decision No. 69 / PUU-XIII / 2015 the arrangement of the agreement in marriage has changed. This study aims to determine the arrangement of the marriage agreement after the Constitutional Court Decision No. 69 / PUU-XIII / 2015 and knowing the legal consequences for third parties with the existence of a marriage agreement after the issuance of the Constitutional Court Decision No. 69 / PUU-XIII / 2015. The research method used is the Normative research method where the assessment is based on legal materials from the existing literature. The results of the analysis show that the marriage agreement arrangements have changed since the Constitutional Court Decision, where the amendment is that the marriage agreement can be made before or after marriage, applies after marriage unless the parties determine otherwise, and also the marriage agreement can be changed and revoked according to the agreement of the husband and wife. . If the agreement in marriage is registered, the agreement will be enforced for the third party. Couples who want to make a marriage agreement should follow the existing rules so that the marriage agreement is valid and does not harm third parties.